Heterotic effect on performance and body measures of feedlot steers - Machado, Diego Soares; Brondani, Ivan Luiz; Alves Filho, Dari Celestino; Cattelam, Jonatas; Quadros, Arlei Rodrigues Bonet de; Silva, Viviane Santos da; Cardoso, Gilmar dos Santos; Borchate, Daniele (Revista de Ciências Agroveterinárias, 2015)
The objective of this study was to evaluate the heterotic effect on performance and body measurements of Charolais (Ch) and Nellore (Ne) steers and crossbreeds from the fifth (21/32Ch 11/32Ne; 21/32Ne 11/32Ch) e sixth (43/64Ch 21/64Ne; 43/64Ne 21/64Ch) generation, feedlot finished. For initial weight, the heterotic effect was 45.9 and 39.1 kg in the fifth and sixth generation, and 41.6 and 38.1 kg for the fi nal weight, respectively, in the same order. For the average daily gain, the heterotic effect was significant in the fifth generation (0.18 kg). Heterotic effect was observed in the initial rump height in the fifth generation (6.14 cm), and in the fifth and sixth generation on final rump height, with values of 5.57 and 4.75 cm, respectively, taking into account the heterotic effect. In relation to withers height, the heterotic effect was significant on fifth and sixth generations for the initial measurement, 7.36 and 7.12 cm, respectively, and finally, 5.19 and 4.33 cm, in the same order, and on withers growth on sixth generation (-2,79 cm). For the initial length, the heterotic effect was 7.60 and 5.72 in the fifth and sixth generations, and negative in fifth (-5.29 cm) and sixth (-3.75 cm) generations for the length of growth. For thoracic perimeter, on initial measurement heterotic effect was observed on both generations, being 10.2 cm on the fifth and 8.05 on the sixth generation, however for the final measurement the heterotic effect was significant only on the fifth generation (6.00 cm). The initial measurement with the highest correlation with the average daily gain was the length (r=0.47; p=0.0007), and with the final weight was the thoracic perimeter (r=0.89; p<0,0001).